A Psycholinguistic Study on Lavender Language - CHADLI, DJAMEL (My University, 2017)
The aim of this study is to discover the language used by gay people. In this regard, this dissertation deals with the issue of to what extent does language affects child’s psychological state and if it is the case, can we reverse this process through language. To answer this problematic, series of suggested answers are presented. First, the influence of language can affect the child’s psychological state since childhood. Second, we either can or cannot reverse this process through language; it depends on the gay’s educational factor. As far as the methodology conducted in this research, a qualitative method is obtained. The latter, is a descriptive study on an interview made with various participants (three gay people from different social backgrounds, three psychologists and some people from general public). The aforementioned participants were under different interview sessions, where they answer set of directed questions. By using this method to analyze the collected data, it is realized that language has an impact on psychological state of the human being and also, we recognized that people have different opinions on gay identity in general.
Case Study: Gay People in Mostaganem City
Keywords: Language; Psychology; Gender; Identity; Gay; Community; Sexuality